Myocarditis in arrhythmogenic right ventricular dysplasia. A casual finding or a part of the disease pathophysiology? - Ana Margarida Barrigó Fernandes Bernardo; Ana Rita Santos; Bruno Piçarra; João Pais; Mafalda Carrington; José Aguiar (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2020)
Myocarditis in Arrhythmogenic Right Ventricular Dysplasia (ARVD) is characterized massive inflammatory cell infiltrates founded after acute myocardial necrosis in the early stages of the disease. This inflammatory response didn't mean necessarily an infective process and could lead to changes in phenotype and to an abrupt progression of the disease.